Re-expression of voltage-gated sodium channel subtype Nav1.3 in the substantia nigra after dopamine depletion. (20th November 2018) - Wang, Ziyi; Kuang, Ping; Lin, Yuying; Liu, Weitang; Lao, Wenwen; Ji, Yonghua; Zhu, Hongyan
Highlights: Nav1.3 was abundantly re-expressed in the SN in 6-OHDA lesioned rats. Nav1.3 was re-expressed in dopaminergic neurons in the SN. Nav1.3 was also re-expressed in neural progenitor cells in the ipsilateral SN. Abstract: Abnormal synchronized oscillatory bursts occurring in the basal ganglia (BG) are suggested to be correlated with motor symptoms in Parkinson's disease (PD) patients and animal models of PD. Voltage-gated sodium channels (VGSCs) have been demonstrated to play an important role in the abnormal electrical activity of neurons in the BG. Nav1.3, a VGSCs subtype, is predominantly expressed in embryonic and neonatal nervous system but barely detected in the normal adult nervous system in rodents. Here we investigated the expression patterns of Nav1.3 in the BG of 6-OHDA lesioned Sprague Dawley rats. The results showed that Nav1.3 at mRNA and protein levels was abundantly re-expressed in the ipsilateral and contralateral SN at 49 days postlesion, but was rarely detected in the other nuclei of the BG in the 6-OHDA lesioned rats. Furthermore, Nav1.3 was not only expressed in TH-positive dopaminergic neurons of the ipsilateral and contralateral SN, but also in nestin-positive neural progenitor cells surrounding the ipsilateral SN and the midline region adjacent to the ipsilateral SN in the midbrain at 49 days postlesion. These results suggested that the re-expression of Nav1.3 may influence the electrical activity of dopaminergic neurons in the SN in 6-OHDA lesioned rats.